2020
DOI: 10.1021/acs.molpharmaceut.0c00075
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody 2C5-Modified Mixed Dendrimer Micelles for Tumor-Targeted Codelivery of Chemotherapeutics and siRNA

Abstract: Targeted delivery of chemotherapeutics to tumors has the potential to reach a high dose at the tumor while minimizing systemic exposure. Incorporation of antibody within a micellar platform represents a drug delivery system for tumor-targeted delivery of antitumor agents. Such modified immunomicelles can result in an increased accumulation of antitumor agents and enhanced cytotoxicity toward cancer cells. Here, mixed dendrimer micelles (MDM) composed of PEG2k-DOPE-conjugated generation 4 polyamidoamine dendrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The most frequently used synthetic polymers for TO delivery contain but are not limited to polyethylenimine (PEI), poly( l -lysine) (PLL), poly(β‐amino ester) (PβAE), polyamidoamine (PAMAM) dendrimers ( Fig. 3 b) [ [187] , [188] , [189] , [190] , [191] , [192] , [193] , [194] , [195] ]. One common feature of these polymers is that they all contain primary or tertiary amino groups that are protonable.…”
Section: Nanoparticles-based Delivery Of Tosmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently used synthetic polymers for TO delivery contain but are not limited to polyethylenimine (PEI), poly( l -lysine) (PLL), poly(β‐amino ester) (PβAE), polyamidoamine (PAMAM) dendrimers ( Fig. 3 b) [ [187] , [188] , [189] , [190] , [191] , [192] , [193] , [194] , [195] ]. One common feature of these polymers is that they all contain primary or tertiary amino groups that are protonable.…”
Section: Nanoparticles-based Delivery Of Tosmentioning
confidence: 99%
“…It was found that the interactions of electrostatic oligodeoxynucleotide-dendrimer complexes were sensitive to pH as well as the ionic strength, and the maximal interaction occurred at low pH and ionic strength [ 202 ]. PAMAM dendrimers have inner cavities and peripheral functional groups, which that can be modified into physically embedding or covalently conjugate drugs with high curative effect [ 203 ], so as to become a promising platform for the co-delivery of genes and other drugs [ 188 , 204 , 205 ]. In addition, PAMAM dendrimers can be combined with other polymers to approach specific functionalities, such as sustained delivery of TO.…”
Section: Nanoparticles-based Delivery Of Tosmentioning
confidence: 99%
“…The design of targeted siRNA nanoparticles also has the potential to reduce nonspecific uptake in other cell types. Various targeting agents, e.g., the RGD peptide, [ 39,40 ] transferrin, [ 41 ] hyaluronic acid (HA), [ 42,43 ] and antibodies, [ 44,45 ] have been incorporated onto the siRNA nanoparticles to promote siRNA delivery into cancer cells.…”
Section: Barriers For Sirna Delivery To Target Cells For Effective Camentioning
confidence: 99%
“…Consequently, an overexpression of ABC proteins or MRP1 is correlated with the reduced accumulation of chemotherapy drugs in cancer cells. 12 Thus, by inhibiting MRP1 expression, it would be expected that the reduction in the efflux of drugs would help restore intracellular drug levels required to induce apoptosis or cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%